2019
DOI: 10.2174/1573395514666180605083448
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal CD4 Depletion in HIV / SIV Infection

Abstract: Among the most significant findings in the pathogenesis of HIV infection was the discovery that almost total depletion of intestinal CD4+ T cells occurs rapidly after SIV or HIV infection, regardless of the route of exposure, and long before CD4+ T cell losses occur in blood or lymph nodes. Since these seminal discoveries, we have learned much about mucosal and systemic CD4+ T cells, and found several key differences between the circulating and intestinal CD4+ T cell subsets, both in phenotype, relative propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 174 publications
1
17
0
Order By: Relevance
“…In contrast, LP GZB + CD4 T cells were readily detected at significantly higher frequencies in PWH versus controls, both as a fraction of total CD4 T cells (PWH: 9.8%, 3.6–22.3; P < .001) ( Figure 1b ) and per area of LP tissue (PWH: 39/mm 2 , 16–104; Controls: 17/mm 2 , 6–33; P = .005) ( Figure 1c ). As expected, percentages of LP CD4 T cells as a fraction of total LP CD3 + T cells, and as the number of CD4 T cells per area of LP tissue, were significantly lower in PWH consistent with gut CD4 T cell depletion 3 (PWH: 17.7%, 12.5–25.7 versus Controls: 72.7%, 62.2–82.7, P < .001; PWH: 400/mm 2 , 226–622 versus Controls: 930/mm 2 , 517–1090, P < .001) ( Figure 1d , e).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, LP GZB + CD4 T cells were readily detected at significantly higher frequencies in PWH versus controls, both as a fraction of total CD4 T cells (PWH: 9.8%, 3.6–22.3; P < .001) ( Figure 1b ) and per area of LP tissue (PWH: 39/mm 2 , 16–104; Controls: 17/mm 2 , 6–33; P = .005) ( Figure 1c ). As expected, percentages of LP CD4 T cells as a fraction of total LP CD3 + T cells, and as the number of CD4 T cells per area of LP tissue, were significantly lower in PWH consistent with gut CD4 T cell depletion 3 (PWH: 17.7%, 12.5–25.7 versus Controls: 72.7%, 62.2–82.7, P < .001; PWH: 400/mm 2 , 226–622 versus Controls: 930/mm 2 , 517–1090, P < .001) ( Figure 1d , e).…”
Section: Resultssupporting
confidence: 81%
“… 1 , 2 Early in infection, HIV-1 replicates to high levels in intestinal CD4 T cells, resulting in the massive depletion of T helper (Th) 17 and Th22 subsets that play critical roles in maintaining intestinal homeostasis. 3 Disruption of gut homeostasis leads to mucosal inflammation and epithelial barrier damage, culminating in increased microbial translocation of enteric bacteria and their inflammatory products into the underlying tissue and systemic circulation. 4 Furthermore, numerous studies, including our own, have demonstrated an altered intestinal microbiome (dysbiosis) among people with HIV-1 (PWH), with dysbiotic profiles correlating with local and systemic immune activation, inflammation and microbial translocation (reviewed in 5 ), metabolic syndrome, 6 and various inflammation-associated comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…24 Profound depletion of IL-17-producing T-helper (Th)17 cells is observed at mucosal barriers early after HIV-1 infection, leading to chronic immune activation. 25 The combi nation of ongoing mucosal inflammation, HIV-1 replication, and M tuberculosis co-infection could result in heightened immune activation leading to constant triggering of the remaining IL-17A-producing cell populations during HIV-tuberculosis co-infection. This possibility is exemplified by findings of upregulated Th17 polarising cytokines and transcription factors in pleural fluid of patients with HIV-tuberculosis co-infection with tuberculosis pleurisy, despite numeric depletion of Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Th1, Th17, and Th22 cells are critically important for initiating primary immune responses and for maintenance of mucosal integrity. Infection and dysregulation of Tfh and other key CD4+ T cell results in hyperactive, yet non-protective immune responses that supports active viral replication and evolution, and thus persistence in host tissue reservoirs (Veazey, 2019). Chronic HIV infection is characterized by Th1 and Th2 production (Gorenec et al, 2016).…”
Section: T Cells and Human Immunodeficiency Virus Type 1 (Hiv-1)mentioning
confidence: 99%